Exploring electronic Word-of-Mouth (eWOM) for healthcare services in Singapore - Lee, Lay Lay (2020)
Healthcare services have transformed over the years. Owing to advancements in the internet and healthcare technology, patients have become more well-informed and are able to take a more proactive approach in making informed personal healthcare decisions through electronic word-of-mouth (eWOM). The role of a physician has evolved gradually from being seen as the holder of a “single source of truth” to a facilitator in helping patients to sift through a myriad of sources of medical information. eWOM allows the exchange of information among healthcare providers, patients, and their families in a broader and more comprehensive way. There is very limited empirical research on the usage of eWOM in healthcare services. Hence, the purpose of this research is to explore eWOM in healthcare services. Singapore has been chosen as the focus of our study, as the high speed network available enables individuals to get connected wherever they go. From a theoretical aspect, this study integrates the principle of value co-creation with a framework on eWOM in healthcare services consisting of three stages: Creation, Spread, and Impact. Criteria attributed to eWOM will be examined at the Creation stage. At the Spread stage, the motives of patients using eWOM will be studied. Lastly, at the Impact stage, how eWOM affects patients’ healthcare decisions and the impact of eWOM on healthcare services will be carefully examined.